Continued circulation of mpox: an epidemiological and phylogenetic assessment, European Region, 2023 to 2024 - Vaughan, Aisling M; Afzal, Mohammed; Nannapaneni, Priyanka; Leroy, Mathias; Andrianou, Xanthi; Pires, Jeffrey; Funke, Silvia; Roman, Celine; Reyes-Uruena, Juliana; Aberle, Stephan; Aristodimou, Aristos; Aspelund, Gudrun; et al. (Euro surveillance : bulletin Europeen sur les maladies transmissibles European communicable disease bulletin, 2024)
During the summer of 2023, the European Region experienced a limited resurgence of mpox cases following the substantial outbreak in 2022. This increase was characterised by asynchronous and bimodal increases, with countries experiencing peaks at different times. The demographic profile of cases during the resurgence was largely consistent with those reported previously. All available sequences from the European Region belonged to clade IIb. Sustained efforts are crucial to control and eventually eliminate mpox in the European Region.
Keywords: dospělí; Female; Europe; dítě; předškolní dítě; Adult; mladý dospělý; ženské pohlaví; Adolescent; lidé; Evropa; surveillance populace; Phylogeny; Incidence; Disease Outbreaks; Male; incidence; Aged; Young Adult; Child, Preschool; Population Surveillance; lidé středního věku; epidemický výskyt choroby; Child; senioři; mužské pohlaví; fylogeneze; Middle Aged; mladiství; Humans